2016
DOI: 10.1007/s00405-016-3958-9
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae biofilm formation in chronic otitis media with effusion

Abstract: Otitis media with effusion (OME) is a highly prevalent disease in children, but the exact pathogenesis and role of bacteria are still not well understood. This study aimed to investigate the presence of otopathogenic bacteria in the middle ear effusion (MEE) and adenoid of children with chronic OME (COME), and to investigate in vivo whether these bacteria, especially Haemophilus influenzae, are organized as a biofilm in the middle ear fluid. MEE and adenoid samples were collected from 21 patients with COME. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
0
24
0
3
Order By: Relevance
“…Bacterial biofilms (that is, colonization of bacteria embedded in the extracellular matrix and adherent to a surface), which are known to protect bacteria against antibiotic treatment 56,57 and the host's immune response, have been demonstrated in the middle ears of patients with CSOM 58,59 , persistent OME 58,60 and those with OM who have failed antibiotic treatment 60 . Biofilms have been reported to occur in MEE 60 , attached to the middle ear mucosa 61 .…”
Section: Bacterial Colonization and Biofilmsmentioning
confidence: 99%
“…Bacterial biofilms (that is, colonization of bacteria embedded in the extracellular matrix and adherent to a surface), which are known to protect bacteria against antibiotic treatment 56,57 and the host's immune response, have been demonstrated in the middle ears of patients with CSOM 58,59 , persistent OME 58,60 and those with OM who have failed antibiotic treatment 60 . Biofilms have been reported to occur in MEE 60 , attached to the middle ear mucosa 61 .…”
Section: Bacterial Colonization and Biofilmsmentioning
confidence: 99%
“…Hall‐Stoodley et al demonstrated biofilms in biopsy specimens from the middle ears of children undergoing tympanostomy tube placement for chronic OME and/or recurrent otitis media but not in those of control children undergoing cochlear implantation . Later, Van Hoecke et al detected the presence of Haemophilus influenzae‐ specific biofilm structures in culture‐positive but not culture‐negative middle ear effusions using fluorescence in situ hybridization . Ours is the first investigation to identify and quantitate two essential biofilm structural components, IHF and HU, within effusions recovered from children with chronic OME.…”
Section: Discussionmentioning
confidence: 99%
“…12 Later, Van Hoecke et al detected the presence of Haemophilus influenzae-specific biofilm structures in culture-positive but not culture-negative middle ear effusions using fluorescence in situ hybridization. 32 Ours is the first investigation to identify and quantitate two essential biofilm structural components, IHF and HU, within effusions recovered from children with chronic OME. Previous work has already shown that biofilms formed by nontypeable Haemophilus influenzae contain eDNA organized into a mesh-like lattice, with bacterial DNABII DNA-binding proteins located at the vertices of crossed strands of eDNA.…”
Section: No Growth 13mentioning
confidence: 99%
“…Esta área de investigación tiene su base en la existencia de biofilms bacterianos en el oído medio y, sobre todo, en las adenoides que podrían tener relación con la OMS y la OMA, actuando como reservorio de patógenos, lo que podría abrir nuevas opciones terapéuticas (Tawfik et al, 2016;Van Hoecke et al, 2016;Davcheva-Chakar et al, 2015: 71-76).…”
Section: • Probióticos E Interleukinasunclassified